ADOPSI TELEMEDICINE DI ERA NEW NORMAL - Dewi, Made Santika; Sunariani, Ni Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Telemedicine is the provision of health services that carried out indirectly due the limitation of distance between health workers and patients, health workers implementing information and communication technology to reciprocal information about diagnosis, treatment, disease prevention as far as research and further evaluation. This research aims to determine and examine mountainously about the perception of medical personnel and patients through telemedicine service of the new normal era. This research used qualitative method with research subject namely doctor and patient. Data collection technique was carried out by in-depth interview. Researchers implement the adoption theory of Davis's technology and Zeithaml and Bitner's Servqual Technique. The result of data analysis in this study indicate that the quality of service through WhatsApp platform from the aspect of tangible, reliability, assurance and empathy are considered adequate especially non-emergency cases based on perceived ease of use, perceived usefulness, behaviour intention to use, actual system usage, attitude toward medical personnel have shown acceptance models upon non-emergency case.